2017
DOI: 10.31235/osf.io/dtrej
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity Regimes and Racial Inequality: A Case Study of Diversity University

Abstract: Despite record investment in diversity infrastructure, racial inequality persists in higher education. This article examines, through a case study of diversity’s articulation process, how diversity is defined, organized, and implemented within an American public flagship university. My findings reveal what I characterize as a diversity regime: a set of meanings and practices thatinstitutionalizes a benign commitment to diversity, and in doing so obscures, entrenches, and even intensifies existing racial inequa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Schools that discuss “diversity beyond race” exhibit the expansiveness of diversity discourse and its many forms. This category aligns with the “condensation” found in James M. Thomas’s (2018a:145) diversity regimes in which “seemingly unrelated phenomena, or signifiers, are condensed under the sign, ‘diversity’.” This category is not without nuance. Institutions who discuss diversity as beyond race either include race as one dimension or use the term diversity broadly to leave room for interpretation.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Schools that discuss “diversity beyond race” exhibit the expansiveness of diversity discourse and its many forms. This category aligns with the “condensation” found in James M. Thomas’s (2018a:145) diversity regimes in which “seemingly unrelated phenomena, or signifiers, are condensed under the sign, ‘diversity’.” This category is not without nuance. Institutions who discuss diversity as beyond race either include race as one dimension or use the term diversity broadly to leave room for interpretation.…”
Section: Resultssupporting
confidence: 69%
“…College students themselves argue that their universities are more likely to promote diversity programs (e.g., multicultural weeks) on their websites rather than delve into issues even more pressing to minority students, such as campus climate (Lowe et al 2013). The effect is a regime that helps to “institutionalize a benign commitment to diversity, [that] obscures, entrenches, and even intensifies existing racial inequality” (Thomas 2018a:143). The result, moreover, is one in which diversity efforts center more so on intent rather than results, celebration rather than inclusion, and commodification rather than representation (Embrick 2011; Smith and Mayorga-Gallo 2017).…”
Section: Diversity and Rationalization In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who tend to benefit from DEI initiatives (e.g., underrepresented racial/ethnic groups, female, LGBQI+, and people with a disability) will conclude such efforts are tokenistic if existing hierarchies remain, 29 as initiatives come and go. Prior studies in higher education have found that a lack of consistent leadership commitment, coupled with a lack of lived experience of historical and structural exclusion, also undermines the effectiveness of DEI workplace initiatives 29–31 …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in higher education have found that a lack of consistent leadership commitment, coupled with a lack of lived experience of historical and structural exclusion, also undermines the effectiveness of DEI workplace initiatives. [29][30][31] Our participants may have also perceived their workplace initiatives as superficial because they more often observed their organizations conducting "planning" rather than "implementation." For example, only about one-fourth of our participants witnessed initiatives that directly support historically and structurally excluded HSPRers, such as mentorship, networking opportunities, and pathway programs.…”
Section: Professional Discriminationmentioning
confidence: 99%